Service Quality and Accounting Efficiency Affecting to Loyalty Using Accounting Office Services of Small and Medium Enterprises (SMEs) in Nakhon Pathom Province - Sonpakdee, Chudapon (Journal of Applied Economics and Management Strategy, 2025)
This research study examines the service quality and accounting efficiency that affect loyalty in using accounting office services of small and medium-sized enterprises (SMEs) in Nakhon Pathom Province. The sample group consists of 390 SME operators in Nakhon Pathom province, and a questionnaire was used as the data collection tool. The statistical methods used for data analysis include descriptive statistics, such as mean and standard deviation, and inferential statistics, which involve multiple regression analysis and Pearson’s correlation coefficient analysis at a statistical significance level of 0.05. The results revealed the quality of service that significantly affects client loyalty to accounting services are in five areas: 1) Tangibility, 2) Reliability, 3) Responsiveness, 4) Assurance, and 5) Empathy. Additionally, the efficiency of accounting practices influences loyalty in three areas: 1) Relevance, 2) Faithful Representation, and 3) Verifiability also affects customer loyalty in accounting firm services. Therefore, accounting offices and related agencies should prioritize both the quality of service and the efficiency of accounting practices in order to develop appropriate management models, strategic plans, and service delivery methods. This will also contribute to enhancing the competency of accounting professionals and improving their overall quality.